P50 Improved access to full polysomnography enhances the diagnostic capability of sleep service. (December 2018) - Zainudin, L; Boylan, C; Cooper, BG; Rauf, F; Wharton, S; Madathil, SC; Huq, S
Abstract : Introduction: Full video polysomnography (PSG) remains the gold standard for the diagnosis of sleep disorders including sleep-disordered breathing (SDB). However, it is resource intensive and not widely available. Most UK sleep centres use domiciliary cardiorespiratory studies for evaluation of SDB. The aim of our study was to assess the impact of faster access to PSG on our sleep service. Method: Domiciliary oximetry and cardiorespiratory studies (Embletta) are undertaken to investigate SDB in our sleep service, based in a university teaching hospital receiving more than 1000 sleep referrals/year. PSG±multiple sleep latency tests are performed for symptomatic patients with normal cardiorespiratory studies, or where there is a suspicion of non-respiratory sleep disorder (NRSD). However, because of lack of ring-fenced PSG beds (PSGs undertaken in elective neurology ward beds), the average capacity is limited to two PSGs/month. In collaboration with a neighboring hospital having a sleep laboratory with four dedicated PSG beds daily, we introduced a change in our pathway whereby we could directly access their PSG service. Retrospective data was collected for the year preceding (November 2015 – October 2016) and following (November 2016 – October 2017) the change. Results: Although the total number of sleep clinic referrals remained largely unchanged over the two years, the number of PSG referrals increased threefold. The median waiting time for PSG reduced significantly from 455 to 77 days. The proportion of cases where PSG revealed a definitive diagnosis (SDB or NRSD) rose from 23% to 55%. In 24% of cases in the second year PSG revealed significant SDB which was missed on previous cardiorespiratory studies. Conclusion: Referring to a sleep laboratory with dedicated PSG beds greatly reduced waiting times and led to increased utilization of PSG in our diagnostic pathway. Consequently, this reduced our overall diagnostic waits and enhanced our diagnostic accuracy – not only for NRSD but also in identifying SDB missed on previous cardiorespiratory studies. Non-diagnostic cardiorespiratory studies, suspicion of NRSD, and persistent symptoms despite treatment should lead to PSG evaluation. Regional networks can be established to gain easier access to PSG, enhancing the diagnostic capability of sleep services.